2019
DOI: 10.1088/1742-6596/1387/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pollinator insect visitation on flower development and productivity of chilli plant

Abstract: This research aimed to find out; (1) the pollinator insect diversity of chili plant; and (2) the effect of pollinator insect visitation on flower development and productivity of chili plant. This experimental study was designed with a factorial completely randomized design. The independent variable was visitation of pollinator insect on plant, while the dependent variables were pollinator insect diversity, flower development, and productivity of chili plant. Each treatment consisted of 5 replicating plots, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The research results by Landaverde-González et al, (2017) also showed that bees from the genus Lasioglossum were the most abundant group in cayenne fields compared to other bee species. Aminatun et al (2019) also reported that Lasioglossum bees are pollinators in cayenne pepper. Meanwhile, Ercan & Onus (2003), Vishwakarma &Singh (2018), andSoli et al (2020) reported that Megachile bees pollinate cayenne and can even produce better yields and fruit quality.…”
Section: Discussionmentioning
confidence: 92%
“…The research results by Landaverde-González et al, (2017) also showed that bees from the genus Lasioglossum were the most abundant group in cayenne fields compared to other bee species. Aminatun et al (2019) also reported that Lasioglossum bees are pollinators in cayenne pepper. Meanwhile, Ercan & Onus (2003), Vishwakarma &Singh (2018), andSoli et al (2020) reported that Megachile bees pollinate cayenne and can even produce better yields and fruit quality.…”
Section: Discussionmentioning
confidence: 92%
“…2022), ants (Aminatun et al . 2019), butterflies (Putra et al . 2021), and beetles (Wanza‐Soli et al .…”
Section: Discussionmentioning
confidence: 99%
“…Solanaceae includes 150 genera and approximately 2,500-3,000 species (Lorenzi & Souza 2012) whose flowers offer large quantities of pollen (pollen flowers; Vogel 1978), or pollen and small amounts of nectar. Although mostly beepollinated (Palma et al 2008;Kiatoko et al 2014;Deyto & Cervancia 2022), other pollinator groups, such flies, wasps, thrips, butterflies, ants, and beetles, successfully pollinate Solanaceae flowers (Aminatun et al 2019;Wanza-Soli et al 2020 Zameer et al 2022). Solanaceae is one of the most important angiosperm families in the world, with third highest economic value, and first among nutritionally relevant vegetables (Wilf et al 2017;Baldrich et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollinator insects increase fertilization rate in flowering plants by transferring pollen from anther to stigma within a flower or between flowers of the same plant or different plants of the same species. Aminatun et al (2019) reported that nine species of pollinator insects visited the flowers of chili plants with a view to feeding, pollen collection, and warmth.…”
Section: Introductionmentioning
confidence: 99%